Pengaruh Kualitas Pelayanan dan Kepuasan Mahasiswa terhadap Profitabilitas STIE Pemuda Surabaya - Ardelia Ratnadewati; Lis Setyowati (Global Leadership Organizational Research in Management, 2023)
This research aims to analyze the influence of service quality and student satisfaction on profitability at STIE Pemuda Surabaya. The research method used is a quantitative method through distributing questionnaires, with a population of 426 and a sample of 100 respondents, based on the Slovin formula. This type of research uses quantitative research. The analysis techniques used in this research are descriptive statistical analysis, classical assumption testing, multiple linear regression analysis, and hypothesis testing. This shows that the size of the quality of campus services has an effect on profitability. Meanwhile, student satisfaction does not have a partially significant effect on profitability. This shows that the lower student satisfaction, the lower the profitability will be. Meanwhile, service quality and student satisfaction simultaneously have a positive effect on profitability.